Study On Assessment Of Drug-Related Problems In Community Pharmacies (Journal of Pharmaceutical Negative Results, 2022)
For preventing Drug-related Problems (DRPs), Pharmacist-led medication reviews have been exhibited. Still, for executing medication reviews, data is very less regarding the execution in routine care, the conditions for sharpening the service along with the community pharmacists’ practical skills. In pharmaceutical care, DRP is a vital word. For the similar concept like medication errors, other words can be wielded however, this word differs from DRPs. During prescribing, dispensing, or administrating medicines, it can begin. Thus, analysis of potential DRPs amongst prescriptions, appraisal of the medication, analogizing the discovered DRPs in Urban and Rural (UR) Community Pharmacies (CP), appraisal of the severity of DRPs amongst prescriptions, usage in geriatric patients centered on Beers Criteria (BC) along with finding the relationship amongst the sort and number of issues detected within the gender, age and number of prescribed drugs in patients has been addressed here. Additionally, the entire DRPs determined, diagnoses linked with DRPs, and the DRPs detected utilizing the Pharmaceutical Care Network Europe (PCNE) are evaluated.